The Effectiveness of Android-Based Applications to Increasing Knowledge of Adolescents on Reproductive Health - Erika Yulita Ichwan; Shentya Fitriana; Diana Hartaty Angraini; Deas Nurul Awaliyah (Jurnal Ilmu dan Teknologi Kesehatan, 2020)
Adolescence is a transition period with specific needs for growth and development. The reproduction of health education is essential to be given to adolescents because they are susceptible to the risks of reproduction health problems. Giving explanations of health education for adolescents by using media will maximize them in absorbing information since media has become an integral part of adolescents' life. One alternative media that is close and familiar with adolescents is an Android application that can be easily accessed by teenagers who have it through a handphone. The purpose of this study was to know the effectiveness of android based applications at the Central Jakarta Senior High School. The method of this research is a quasi-experimental research with control group design. Sampling by cluster sampling method at SMAN 1 Jakarta as an intervention group and SMAN 5 Jakarta as a control group. Statistical tests using the Paired T-Test, Wilcoxon Test, and Mann Whitney test. The results of the study show what is meant by the knowledge of adolescents with a value of p = 0,000, so Android application can be applied as a media tool about improving the health of adolescents in schools.